Intestinal carriage of colistin-resistant Enterobacteriaceae at Saint Georges Hospital in Lebanon. (June 2020) - Nawfal Dagher, Tania; Al-Bayssari, Charbel; Chabou, Selma; Baron, Sophie; Hadjadj, Linda; Diene, Seydina M.; Azar, Eid; Rolain, Jean-Marc
Highlights: Colistin-resistant Gram-negative bacteria were detected in patients in Lebanon. These were isolated from patients who received colistin and carbapenem combination therapy for more than 1 week. There was an absence of mcr-1/2/3/4/5 genes. Colistin resistance was due to mutation into protein sequences of pmrA/B, phoP/Q, and mgrB . Abstract: Objectives: The increase in resistance to antibiotics has led to the revival of colistin as the last option for treatment, which automatically led to an increase of colistin-resistant, Gram-negative bacteria. In this study, we report the presence of clinical colistin-resistant Enterobacteriaceae isolated from a Lebanese hospital. Methods: From 23 rectal swabs, eight colistin-resistant clinical strains (five Escherichia coli, two Enterobacter cloacae, and one Klebsiella pneumoniae ) were isolated. Antibiotic susceptibility testing was performed using the disk diffusion method and Etest. The broth microdilution method was used to determine colistin susceptibility. Reverse transcription polymerase chain reaction (RT-PCR), standard PCR and sequencing were used to investigate genes encoding for extended-spectrum β-lactamases, carbapenemases and colistin resistance. Genotyping of these isolates was conducted by multilocus sequence typing (MLST). Results: Results of antibiotic susceptibility testing revealed that all isolates were resistant to colistin. They had MICs for colistin that ranged from 8 to 32 mg/L. Real-time PCR results showed that five strains harboured bla TEM-1 and one strain harboured bla TEM-163 . Moreover, four strains were positive for bla CTX-M-15, bla CTX-M-103 and bla CTX-M-189, and K. pneumoniae harboured bla SHV-1 . Observed colistin resistance was linked to amino acid substitutions into protein sequences of pmrA/B, phoP/Q, and mgrB. Interestingly, we report here a mutation in the mgrB regulator and pmrA/B, phoP/Q in colistin-resistant E. cloacae and E. coli clinical isolates for the first time in Lebanon. Conclusion: This study highlights the presence of colistin-resistant Gram-negative bacteria in a Lebanese hospital, which is worrisome. An urgent strategy needs to be adopted to avoid the spread of such bacteria.